Genetic Diversity in Wild Populations of the Scaly-breasted Munia (Lonchura punctulata) - แก้วแสงสุข อำพร; สังฆเมธาวี วังวร; J. Pierce, Andrew; N. Petney , Trevor; สายจันทา วีระชัย (KKU Science Journal, 2015)
We analyzed 290 nucleotide sequences of the mitochondrial NADH dehydrogenase subunit 3 (ND3) gene from 29 samples of Scaly-breasted Munia (Lonchura punctulata) from three natural populations from the north and northeast of Thailand. Eleven variable nucleotide positions were observed. Based on these variations, 14 haplotypes were generated. Low genetic difference among three populations in Thailand was observed and there was no population substructuring related to their geographic distribution. This may be influenced by trading in this species in order to allow its release during Buddhist ceremonies. However, an isolate from Java was highly genetically distinct from those from Thailand, indicating that large geographic distances act as a natural barrier and play an important role in genetic differentiation. Our finding thus provides evidence of a species complex of Scaly-breasted Munia in Southeast Asia. A more comprehensive analysis based on the morphology, biology and genetics of scalybreasted munia from throughout its distribution will be required in order to determine the number of genetically divergent groups present.